SISTEM PEMBERIAN UPAH DI UMKM BINTANG EMAS DESA KASENGAN KECAMATAN MANDING - Widyastuti, Endang; Anwar, Syaiful (LP2M Universitas Bina Bangsa, 2025)
Wages are a fair and worthy reward for workers for their services in achieving organizational goals. Wages are direct financial rewards paid to employees based on hours worked, the number of goods produced or the number of services provided. The amount of wages can vary. Bintang Emas MSMEs are home industries that produce cassava chip products. The Covid-19 Pandemic in 2020 to mid-2022 has had an impact on Bintang Emas MSMEs, where sales have decreased and resulted in a wage system at Bintang Emas MSMEs. The purpose of this study is to find out how the wage system in Bintang Emas MSMEs is.This type of research is qualitative descriptive. The sample of data sources in this study is the owner of Bintang Emas MSMEs as a key informant. The data collection techniques in this study are observation, interviews and documentation. The data analysis techniques in this study are data reduction, data presentation and verification